2024
DOI: 10.1021/acs.energyfuels.4c01065
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Production Characteristics of Deep Coalbed Methane: A Case Study of Daning-Jixian Block

Xuanrui Zhang,
Fengpeng Lai,
Ya Meng
et al.

Abstract: The Daning-Jixian block, located in the eastern margin of the Ordos Basin, is abundant in deep coalbed methane (CBM) resources and serves as a pilot test block for deep CBM development in China. Currently, the exploration and development of a deep CBM are in the early stages. The production characteristics and development laws across different production stages are not fully elucidated, leading to uncertainties in discharge and production control measures as well as the optimization of the production system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Practice has shown that the recovery rate of deep CBM is limited by well-bo om flow pressure [17,18]. Reducing the well-bo om flow pressure can effectively extend the stable production phase of CBM wells and increase the production pressure differential, thereby optimizing productivity and effectively improving the recovery rate [19]. Due to the direct connection of the casing annulus in CBM wells to the gathering and transportation pipeline network for external gas export, it becomes difficult to reduce the well-bo om flow pressure further when it drops to around 4 MPa, significantly impacting the development efficiency of deep CBM.…”
Section: Introductionmentioning
confidence: 99%
“…Practice has shown that the recovery rate of deep CBM is limited by well-bo om flow pressure [17,18]. Reducing the well-bo om flow pressure can effectively extend the stable production phase of CBM wells and increase the production pressure differential, thereby optimizing productivity and effectively improving the recovery rate [19]. Due to the direct connection of the casing annulus in CBM wells to the gathering and transportation pipeline network for external gas export, it becomes difficult to reduce the well-bo om flow pressure further when it drops to around 4 MPa, significantly impacting the development efficiency of deep CBM.…”
Section: Introductionmentioning
confidence: 99%